Synthesis of holey reduced graphene oxide covered in the FeCo@SiO2 and their enhanced electromagnetic absorption properties. (June 2019) - Li, Suping; Huang, Ying; Zhang, Na; Zong, Meng
The FeCo@SiO2 /holey reduced graphene oxide composite was successfully prepared by combining liquid-phase reduction reaction in argon atmosphere with high-temperature calcination. The FeCo@SiO2 /holey reduced graphene oxide composite was characterized by X-ray diffraction, X-ray photoelectron spectroscopy, vibrating sample magnetometer, Fourier transform infrared spectroscopy, Raman spectroscopy, transmission electron microscopy and scanning electron microscopy analysis and exhibit excellent electromagnetic wave absorption properties. The maximum reflection loss of FeCo@SiO2 /holey reduced graphene oxide composite reaches –46.28 dB at 16.16 GHz with the thickness of 1.5 mm and the absorption bandwidth with the reflection loss below –10 dB was up to 3.92 GHz (from 14.08 GHz to 18 GHz) with the thickness of 1.5 mm. The absorption bandwidth with RL below –10 dB is up to 12.64 GHz. It is believed that the FeCo@SiO2 /holey reduced graphene oxide composite can serve as an excellent microwave absorber.